2D‐Fe3O4 Nanosheets for Effective Arsenic Removal. (April 2017) - Luo, Hongxi; Cheng, Fangwei; Hu, Weiming; Wang, Jinpeng; Xiang, Shuting; Fidalgo de Cortalezzi, Maria
Abstract: Fe3 O4 adsorbent with 2D structures was synthesized via solvothermal method and its application in arsenic removal was investigated. Isotherms were generated at pH=4.7 and 7.6 and the results were best fitted by the Freundlich isotherm model; good As(V) adsorption capacity was achieved for the Fe3 O4 adsorbent at both pH values. Furthermore, pH effects were evaluated; the optimal pH value for adsorption was 8.27 with the adsorption capacity and the removal efficiency being 18.55 mg/g and 93.69%, respectively. Based on the measurements of the zeta potential and particle size of the adsorbent, we proposed that the overall pH dependence was a result of the combined effects of the zeta potential, particle size of the adsorbent, and existing form of As(V). From kinetics studies, the As(V) adsorption by Fe3 O4 adsorbent followed the pseudo‐second‐order model and could be described by a two stage mechanism. When initial As(V) concentration was 1 ppm, 73% of the As(V) was adsorbed within the first 2.5 minutes and an overall removal efficiency of 82.5% was achieved in 2 hours. Increased removal efficiency is expected at higher adsorbent loading, thus allowing the post‐treatment water to meet drinking water quality standards.